Atrial longitudinal strain in cardiac aTTR amyloidosis and occurrence of atrial fibrillation. (4th February 2022) - Merli, E; Ricci Lucchi, G; Anselmi, F; Cicchitelli, G; Fabbri, E; Rubboli, A; Piovaccari, G
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND In systemic amyloidosis cardiac infiltration by amyloid fibrils leads to increased stiffness of the myocardium and of the atrial walls. There is a reduction in left atrial mechanical function and a high risk of thrombi formation. Atrial deformation by speckle tracking echocardiography peak atrial longitudinal strain (PALS) can predict the incidence of atrial fibrillation (AF) and ischaemic stroke in the general population and in patients (pts) with cryptogenic stroke. The predictive value of PALS seems to differ in different pts populations according to the prevalence of ventricular versus atrial myopathy (1). PURPOSE to compare parameters of atrial function in cardiac amyloidosis pts in sinus rhythm (SR) and AF and to observe if they are associated with the occurrence of new onset AF at follow-up (FUP). METHODS between 2016-2021 all pts with diagnosis of cardiac aTTR amyloidosis referred to the Clinic underwent an echocardiographic study including 2D-speckle tracking evaluation of left ventricular and left and right atrial strain. All pts received a regular FUP (clinical, echo, ECG and 24 hours Holter monitoring). Atrial function was evaluated by PALS in all pts and by PALS and PACS (peak atrial longitudinal strain during atrial contraction phase) in pts in SR. RESULTS 47 pts with aTTR cardiac amyloid (39/47 wild-tipe) were studied. Mean age = 82 ± 5 years, LV mass = 190 ± 46 g/m2; LV EF= 53%±9, GLS= -10%±4, EF/GLS ratio=-5, 5 ± 2, left atrial (LA) volume = 49 ± 9 ml/m2, LA PALS 9, 7%±6, 6, right atrial (RA) PALS 15, 9 ± 9, 6. At the time of diagnosis 29 pts were in SR and 18 pts were in AF. Pts in AF had lower PALS (5, 1%±3, 7 in AF pts vs 11, 9%±6, 9 in SR pts, p = 0, 001) and lower (less negative) GLS (-9, 1%±3, 1 in AF pts vs -11, 8%± 4, 2 in SR pts, p = 0, 02). LA volume was not significantly different in AF pts compare to SR pts (51, 4 ml/m2 ± 7, 65 vs 47, 6 ml/m2 ± 10, 9; p = 0, 19). During a median FUP of 21 months 8 pts had a new onset AF. There was no significant difference in atrial size and atrial deformation parameters between pts who had new onset AF at FUP compared to pts who did not (Tab 1). The only parameter associated with new onset AF at FUP was GLS (-8.21%± 2, 8 vs -13.01%±4, 02, CI -10.8—5.6 vs -14.8—11.18, respectively, in pts who developed new onset AF compared to pts who did not, p = 0.007). 5 pts had a cardioembolic stroke at FUP: at the time of the admission for stroke they were all in AF. CONCLUSIONS Our data show that in this group of pts with aTTR cardiac amyloidosis all echo parameters of LA size and function were overall impaired. In this setting of advanced disease LA volume was not significantly different in pts in AF compared to pts in SR and was not associated with new-onset AF at FUP. Deformation parameters were significantly more impaired in pts in AF compared to pts in SR, however PALS was not associated with the occurrence of new onset AF at follow-up. The only parameter associated with the occurrence of new onset AF at follow-up was GLS.